(untitled) (Scientific journal of the Fergana State University, 2024)
During 2022-2023, studies were carried out on invasive species common in 6 rivers and ditches flowing through the Fergana region. It has been established that 8 species of invasive species are common in inland waters of the region. Among them, the most widespread species is Triplophysa strauchii (Kessler, 1874), which is found in all water bodies of the region.